Crosstalk between mitophagy and innate immunity in viral infection - Fu, Cheng; Cao, Nan; Liu, Wenjun; Zhang, Zilin; Yang, Zihui; Zhu, Wenhui; Fan, Shuangqi (Frontiers in Microbiology, 2022)
Mitochondria are important organelles involved in cell metabolism and programmed cell death in eukaryotic cells and are closely related to the innate immunity of host cells against viruses. Mitophagy is a process in which phagosomes selectively phagocytize damaged or dysfunctional mitochondria to form autophagosomes and is degraded by lysosomes, which control mitochondrial mass and maintain mitochondrial dynamics and cellular homeostasis. Innate immunity is an important part of the immune system and plays a vital role in eliminating viruses. Viral infection causes many physiological and pathological alterations in host cells, including mitophagy and innate immune pathways. Accumulating evidence suggests that some virus pro-mote self-replication through regulating mitophagy-mediated innate immunity. Clarifying the regulatory relationships among mitochondrial, mitophagy, innate immunity, and viral infection will shed new insight for pathogenic mechanisms and antiviral strategies. This review systemically summarizes the activation pathways of mitophagy and the relationship between mitochondrial and innate immune signaling pathways, and then discusses the mechanisms of viruses on mitophagy and innate immunity and how viruses promote self-replication by regulating mitophagy-mediated innate immunity.